Biosynthesis of Gold Nanoparticles by Vascular Cells in vitro - Kitching, Michael; Inguva, Saikumar; Ramani, Meghana; Gao, Yina; Marsili, Enrico; Cahill, Paul (Frontiers in Microbiology, 2022)
Biosynthesis of gold nanoparticles (AuNPs) for antimicrobial and chemotherapeutic applications is well established in microbial hosts such as bacterial, fungi and plants to some extent. However, reports on AuNPs biosynthesis in mammalian cells are scarce. In this study, bovine aortic endothelial and bovine aortic smooth muscle cells were examined for their ability to synthesize AuNPs in vitro. Cell culture conditions such as buffer selection, serum concentration and initial Au3+ concentration were optimized. The biosynthesized AuNPs were characterized through visible spectrometry, transmission electron spectroscopy, X-ray diffraction, and Fourier transform infra-red spectroscopy. AuNPs produced are semi-crystalline in nature. Bovine aortic endothelial cells and bovine aortic smooth muscle cells produced small, spherical AuNPs with a similar diameter (23±2nm and 23±4nm, respectively). Hydrogen peroxide pre-treatment increased AuNP synthesis, suggesting that oxidative stress may contribute to the reduction Au3+ ions. However, buthionine sulfoximine inhibition of glutathione synthesis, a key regulator of oxidative stress, failed to affect AuNP generation. Taken together, these results show that under the right synthesis conditions, non-tumour cell lines can produce detectable concentrations of AuNPs in-vitro.